Use of gas cluster ion source depth profiling to study the oxidation of fullerene thin films by XPS - James McGettrick (Organic Electronics, 2017)
The analysis of organic materials such as phenyl-C61-butyric acid methyl ester (PC61BM) by depth profiling is typically fraught with difficulty due to the fragile nature of the sample. In this work we utilise a gas cluster ion source for the controlled depth profiling of organic materials that would historically have been too fragile to analyse and obtain quantitative compositional data through the whole thickness of the film. In particular we examine the oxygen diffusion and photo-oxidation kinetics of one of the most commonly used electron acceptor materials for many organic optoelectronic applications, namely PC61BM, in both neat films and in blends with polystyrene. Exposure to AM1.5G light and air under ambient conditions, results in a higher level of surface oxidation of blended PC61BM:polystyrene than is observed for either pure control film. Gas cluster ion source depth profiling further confirms that this oxidation is strongest at the extreme surface, but that over time elevated oxygen levels associated with oxidised organic species are observed to penetrate through the whole blended film. The results presented herein provide further insights on the environmental stability of fullerene based organic optoelectronic devices.